KAJIAN SISTEM PENGENDALIAN RISIKO KREDIT DALAM PELAKSANAAN AUDIT BERBASIS RISIKO (KASUS PADA KANTOR CABANG BANK) - HC Royke Singgih; Eriyatno Eriyatno; Heny K. Daryanto; Dedi Budiman Hakim (Jurnal Manajemen & Agribisnis, 2012)
The purpose of this study was to evaluate a credit risk control system to implement risk-based audit (RBA). The case was conducted in three stages using system approach. The first stage was to identify the factors influencing the effectiveness RBA implementation. Identification process was conducted through gap observation and exploration to determine key factors derived through gap analysis comparing the empirical outcome of the effectiveness credit management process from the expectation outcome. The second stage was using Exponential Comparison Method (ECM) which produces the ranking and the priority of the key factors through experts with in-depth interview which is the paramount importance steps to evaluate. The third stage was using Analytical Hierarchy Process (AHP) techniques, involving the experts with questionnaire and in-depth interview to decide the best, suitable alternative strategies to cope with the negative gap, to reach the goals expected which is to minimize the gap. There were four components mentioned to complete and to detect the gap, which credit operation, human resource knowledge, organization, and supporting system/IT. The output of this study was a credit risk control system for the bank. The study has limitation, due to the scope of the region of the bank, and the risk mapping only for credit risk. The preposition of the study, that the application of the system will enhance the implementation of risk-based audit model.Keywords: Exponential Comparison Method/ECM, Key Factors, Study, Credit Risk Control, AHP, Risk-Based Audit